2008
DOI: 10.1186/1756-6606-1-17
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal enzyme cathepsin D protects against alpha-synuclein aggregation and toxicity

Abstract: α-synuclein (α-syn) is a main component of Lewy bodies (LB) that occur in many neurodegenerative diseases, includingParkinson's disease (PD), dementia with LB (DLB) and multi-system atrophy. α-syn mutations or amplifications are responsible for a subset of autosomal dominant familial PD cases, and overexpression causes neurodegeneration and motor disturbances in animals. To investigate mechanisms for α-syn accumulation and toxicity, we studied a mouse model of lysosomal enzyme cathepsin D (CD) deficiency, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
236
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(254 citation statements)
references
References 75 publications
(92 reference statements)
15
236
2
1
Order By: Relevance
“…13,14 Genetic models of cathepsin D-deficient animals accumulate alpha-synuclein and autophagic vesicles. [15][16][17] Both LAMP2 and cathepsin D mutations affect not only the lysosomes but also autophagy and lipid metabolism, [18][19][20] further emphasizing the potential value of an integrated analyses of genes, biological pathways and disease connections. Furthermore, loss-of-function mutations in NPC1 and NPC2 that encode lysosomal acid sphingomylenases lead to Niemann-Pick Type C (NPC) disease, with accumulation of cholesterol and other lipids in late endosomes and lysosomes in virtually every tissue including the brain.…”
Section: Resultsmentioning
confidence: 99%
“…13,14 Genetic models of cathepsin D-deficient animals accumulate alpha-synuclein and autophagic vesicles. [15][16][17] Both LAMP2 and cathepsin D mutations affect not only the lysosomes but also autophagy and lipid metabolism, [18][19][20] further emphasizing the potential value of an integrated analyses of genes, biological pathways and disease connections. Furthermore, loss-of-function mutations in NPC1 and NPC2 that encode lysosomal acid sphingomylenases lead to Niemann-Pick Type C (NPC) disease, with accumulation of cholesterol and other lipids in late endosomes and lysosomes in virtually every tissue including the brain.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, multiple transgenic lines were generated to further characterize the role of other cathepsin family members in neuroprotection. We found that overexpression of Cathepsin B or Cathepsin L, as well as 2 enzymatic CD mutants, failed to protect worm DA neurons against α-syn neurodegenedration, demonstrating that this effect is both specific to CD and contingent based on its enzymatic function [31] (Fig. 3a).…”
Section: Usefulness Of C Elegans α-Synuclein Model For Analysis Of Nmentioning
confidence: 88%
“…3 The Caenorhabditis elegans α-synuclein model is predictive for gene analysis in dopamine (DA) neuroprotection assays (a). Gene products identified in mammalian systems can be further evaluated for efficacy in protecting DA neurons from α-synuclein-induced DA neurodegeneration by overexpression in C. elegans DA neurons [23,31]. (b) Yeast screens for suppressors of α-synuclein toxicity have yielded gene candidates that were subsequently examined in C. elegans and drosophila for the ability to reduce the neurodegeneration associated with α-synuclein overexpression.…”
Section: Chemical Modifiers Are Readily Analyzed In C Elegans α-Synumentioning
confidence: 99%
“…Z-Phe-Aladiazomethylketone, a positive modulator of cathepsin B activity, reduces Aβ levels in 10-11-month-old APP mice with Swedish and Indiana mutations (APP Swe/Ind ) and in 20-22-month-old APP swedish /PS1ΔE9 mice, protects against synaptic degeneration, and mitigates behavioral deficits [212]. Similarly, cathepsin D, another lysosomal/endosomal enzyme, has been implicated in clearance of Lewy bodies in PD [220]. One way to pharmacologically enhance cathepsin B and D activity is by administering pharmacological chaperones similar to the ones used in lysosomal storage diseases [221].…”
Section: Trehalosementioning
confidence: 99%